EFFECT OF SHADING AND NANO NPK FERTILIZERS ON THE GROWTH OF RUSCUS ACCULATUS PLANT - SHAABAN, BINAHI S.; MOHAMMED, CHINAR S.; YAHYA, HOZAN JASIM (Journal of Duhok University, 2024)
This experiment was conducted in the plastic greenhouse belong to the nursery of Duhok University for the period from 1st Aug. 2021 to 30th May 2022. Aimed to study the effect of shade (0, 50 %) and three concentration (0, 3, 6) g L-1 of Nano NPK fertilizers added twice monthly on the growth of Ruscus acculatus plant. The results showed that 50% of shade increased significantly the Number of branches, leaves area, number of rhizomes growth index, root dry weight, total chlorophyll compared with 0 % shade. Increased Nano NPK fertilizers to 6 g L-1 increased significantly the plant height, number of leaves, leaves area, growth index, Vegetative dry weight compared with the other concentration. The highest Number of branches (22.00) and growth index (84303) was for (50% shading + 3 g l-1) Nano (NPK), number of leaves (1083.3 and 1035.7) and (16515 and 16371) and Vegetative dry weight (52.01 and 47.95) for the (two shades respectively + 6 gl-1), number of rhizomes (10.00) for (50% shading + 6 g l-1), whereas the three conc. of Nano NPK + 50% shade increased significantly the root dry weight compared with other shading levels, finally the best treatment for total chlorophyll was for (50% shade +3 g l-1).